2008
DOI: 10.1088/1126-6708/2008/05/068
|View full text |Cite
|
Sign up to set email alerts
|

Finite temperature behaviour of the ISS-uplifted KKLT model

Abstract: We study the static phase structure of the ISS-KKLT model for moduli stabilisation and uplifting to a zero cosmological constant. Since the supersymmetry breaking sector and the moduli sector are only gravitationally coupled, we expect negligible quantum effects of the modulus upon the ISS sector, and the other way around. Under this assumption, we show that the ISS fields end up in the metastable vacua. The reason is not only that it is thermally favoured (second order phase transition) compared to the phase … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The vacuum selection in meta-stable SUSY breaking models has been discussed in several literature for the ISS-type models [39,40,41,42,43,44,45] and the generalized O'Raifeartaigh models [46,47,48,33,34]. In particular, it was shown in Ref.…”
Section: Vacuum Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vacuum selection in meta-stable SUSY breaking models has been discussed in several literature for the ISS-type models [39,40,41,42,43,44,45] and the generalized O'Raifeartaigh models [46,47,48,33,34]. In particular, it was shown in Ref.…”
Section: Vacuum Selectionmentioning
confidence: 99%
“…For the potential at finite temperatures, we use the one in Eq. (44). The decay temperature is calculated by using the formulae in Refs.…”
Section: S-dominationmentioning
confidence: 99%
“…The presence of minima at high T could also have implications regarding the question how natural it is for the Universe to be in a metastable state at T = 0. More precisely, recent studies of various toy models [221,222,223,224,225] have shown that, despite the presence of a supersymmetric global minimum, it is thermodynamically preferable for a system starting in a high T minimum to end up at low temperatures in a (long-lived) local metastable minimum with broken supersymmetry. Similar arguments, if applicable for more realistic systems, could be of great conceptual value given the present accelerated expansion of the Universe.…”
Section: Thermal Effects In String Compactificationsmentioning
confidence: 99%
“…After briefly recalling the basic ingredients of topological order and topological symmetry breaking and settling some notation, we show how open string operators and the modular S-matrix can be used as order parameters and phase indicators for topological symmetry breaking. We then introduce a class of multi-parameter lattice actions for non-abelian discrete gauge theories and verify the theoretical analysis [18,19] in detail by numerical simulations.…”
Section: Introductionmentioning
confidence: 98%
“…The hidden quantum group symmetry and its representation theory that forms a modular tensor category is a powerful way to characterize the distinct topological phases of pure DGTs and forms the natural basis for the concept of topological symmetry breaking, which is defined as the breaking of quantum group symmetry [17][18][19]. A brief review of this symmetry breaking mechanism is given in section 1.3.…”
Section: Introductionmentioning
confidence: 99%